A simple model for the numerical characterization of spatiotemporal variability in aquatic ecosystems - Gonzalez-Valencia, Rodrigo; Magana-Rodriguez, Felipe; Sepulveda-Jauregui, Armando; Aguirrezabala-Campano, Teresa; Gerardo-Nieto, Oscar; Thalasso, Frederic (My University, 2019)
Aquatic ecosystems are subject to spatiotemporal variations that are important to quantify and understand for a proper assessment of their diversity and complexity. The objective of the present study was to develop a simple model that gives a numerical value to homogeneity and other spatiotemporal attributes for an easier analysis of aquatic ecosystem structure. The model allows for the comparison among different ecosystems, or different periods of time or zones of a given aquatic ecosystem. The model developed sets a numerical value to homogeneity, establishes the fraction of the ecosystem that contains a given percentage of the total amount of a compound, quantifies the fraction of the aquatic ecosystem in which no detectable levels of the measured compound are found, identifies the fraction of the ecosystem that represents an adequate habitat for a given process, and defines a simplified bidimensional vector of heterogeneity. This model is applicable to the two main maps used in the field of limnology: maps showing a particular parameter over two spatial dimensions, and maps showing a particular parameter over one spatial and one temporal dimension. The model was tested with different parameters obtained from three contrasting aquatic ecosystems, a highly polluted Mexican highland reservoir, a naturally acidic German bog lake, and a mesotrophic Patagonian lake.
Keywords: depth-space; depth-time; distribution; homogeneity; maps; methane